The effect of peer lesson strategy on learning outcomes of building construction and land measurement techniques - Sitorus, Heri Franata; Wan Mat, Wan Ameran bin; Sudira, Putu; Sinaga, Enny Keristiana (Jurnal Pendidikan Teknologi dan Kejuruan, 2023)
Peer Learning is a teaching and learning strategy that involves groups of students working together to solve a problem, complete a task, or create a product. Simply putting students in groups and telling them to work together does not mean they know how to work cooperatively. This study aims to determine whether there is an effect of peer lesson learning strategies on learning outcomes in building construction subjects and land measurement techniques, concrete characteristics specification material, in class X students majoring in modeling design and building information of SMK Negeri 1 Lubuk Pakam. The study used quantitative research with experimental research type. The population amounted to 60 students; the research sample was taken by simple random sampling by taking two classes. Class X DPIB-A as the experimental class and class X DPIB-B as the control class. The instrument used to determine student learning outcomes is a multiple-choice test of 36 questions that have been tested for validity and reliability with point biseral correlation techniques. Data analysis used the t-test formula. The results showed that the average post-test score obtained from the experimental class was 75.35 with a high category of 73.33% and the control class was 61.46 with a sufficient category of 76.67%. From the results of the hypothesis testing analysis with a significance level of 5%, the post-test values of the two classes were calculated t_ count t_ table (6.27227 1.671) then Ha was accepted, so that a significant effect was obtained which showed that the learning outcomes of building construction and land measurement techniques were more effectively taught with peer lesson learning strategies than conventional learning models.